Aid and rent-driven growth: Mauritania, Kenya and Mozambique compared - Richard M. Auty (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper conceptualises foreign aid as a geopolitical form of rent in order to help distinguish the conditions under which aid is detrimental to sustained economic recovery from those where it is beneficial. Foreign aid shares with natural resource rent and contrived (i.e., government monopoly) rent the property of being a large revenue stream that is detached from the economic activity that generates it, and elicits political contests for its capture. Rent-driven models suggest such contests have two adverse effects: (i) they deflect government incentives into rent-channelling at the expense of promoting wealth creation; and (ii) the resulting political allocation of the rent distorts the economy and precipitates a growth collapse, which is protracted. In this context, the three principal causes of aid failure identified in the literature (corruption, a poor policy environment and Dutch disease effects) are all symptoms of the destabilizing impact of rent streams on immature political economies. Consequently, the deployment of foreign aid to revive collapsed economies runs the risk of perpetuating rent-seeking and thereby postponing essential economic restructuring. This paper compares the varied impacts of aid on the development trajectories of Mauritania, Kenya and Mozambique. It argues that successful aid deployment requires: recognition that aid modalities differentiate aid's effectiveness; stronger public accountability; and the construction of a cohesive pro-reform political constituency. The paper proposes a dual track strategy as a politically practical means of deploying geopolitical rent to restructure distorted economies. – Africa ; aid ; rent ; resource curse ; economic development
Keywords: H53; O19; O55; 330; Entwicklungshilfe; Rententheorie; Wirtschaftswachstum; Mauretanien; Kenia; Mosambik